Students' View on Grammar Teaching - Male, Hendrikus (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2011)
The focal point of this paper is on the view of the fifth semester students of FKIP UKI on the teaching of English grammar which was gauged through a study conducted in November 2010. The findings of the study, obtained via quantitative and qualitative approaches, revealed that a majority of the respondents basically viewed grammar is important in their study of English. They also viewed knowledge of grammar plays an important role in writing, but has no significant role in speaking. In addition, the respondents seemed to prefer explicit than implicit teaching in their trial to master English grammar. The paper concludes by suggesting the need to explore new approaches to the teaching of grammar to enhance students’ autonomy in learning grammar.